2010
DOI: 10.1021/ef901060u
|View full text |Cite
|
Sign up to set email alerts
|

Speciation Evolutions of Heavy Metals during the Sewage Sludge Incineration in a Laboratory Scale Incinerator

Abstract: With the growing application of sludge incineration, the thermal behavior of heavy metals during this process is increasingly a concern. This work was conducted to determine the speciation evolutions of heavy metals during sewage sludge incineration on a laboratory scale. It was found that the acid-soluble fraction of Zn was more inclined to volatilize. As for Pb and Cr, the volatilization of residual fractions and oxidizable fractions dominated, respectively. For Cu without moisture and Ni, the speciation evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…Heavy metals are still an issue. Some studies have been focused on the speciation of heavy metals in slag from combustion of MSS in laboratory scale experiments (Chen and Yan, 2012;Liu et al, 2010). Yao et al (2010) and Zhao et al (2009) reported the speciation of heavy metals in fly ash and slag during combustion of hospital waste and municipal solid waste ground on field experiments.…”
Section: G R a P H I C A L Abstractmentioning
confidence: 99%
“…Heavy metals are still an issue. Some studies have been focused on the speciation of heavy metals in slag from combustion of MSS in laboratory scale experiments (Chen and Yan, 2012;Liu et al, 2010). Yao et al (2010) and Zhao et al (2009) reported the speciation of heavy metals in fly ash and slag during combustion of hospital waste and municipal solid waste ground on field experiments.…”
Section: G R a P H I C A L Abstractmentioning
confidence: 99%
“…Material dp a (m) a (g/cm 3 measurement was taken, and the specific surface area was assessed from the nitrogen adsorption data according to a partial relative pressure range of 0.05-0.25 using the Brunauer-Emmett-Teller (BET) method [29,30]. The size distribution of the macropores of the samples was determined using digital microscopy equipped with an image analysis system (KH-7700, HIROX) [25,31].…”
Section: Characterization Of the Sorbentsmentioning
confidence: 99%
“…disposal was banned in 2012 to comply with the 1996 Protocol of the London Convention. Thus, new approaches are now required to treat sewage sludge, and these include recycling, biological treatment, and thermal treatment [1,3,4]. In South Korea, the total amount of sewage sludge produced in 2012 was 3653 million tons, and the incineration rate significantly increased from 16% in 2006 to 25.2% in 2012 [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many thermochemical methods in practice have been widely studied, such as combustion, pyrolysis, and gasification (Bridgwater, 2003, Chen et al, 2008, Liu et al, 2010and Ruth, 1998. In particular, fungible transportation fuels can be synthesized over commercialized catalysts using synthetic gas (syngas) from various gasification technologies.…”
mentioning
confidence: 99%